Efecto de la integridad de la cromatina sobre la morfometría de la cabeza del espermatozoide de toro. - Héctor Nava Trujillo; Armando Quintero Moreno; Adirmo Hernández Fernández; Venuslira Vílchez Siu; Carla Osorio Meléndez; Jorge Rubio Guillén; Decio González Villalobos; Geovanny Finol Parra (Revista Científica, 2013)
Ver resumen pdf.